2023
DOI: 10.3390/ani13132176
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Activity of Tanacetum vulgare L. (Leaf and Flower) Extracts against Trichostrongylidae Nematodes in Sheep In Vitro

Abstract: Due to the high prevalence of gastrointestinal nematodes in sheep, the growing anthelmintic resistance, and the development of organic farming systems, sustainable alternatives are being sought. One such method is phytotherapy. This study aimed to evaluate the in vitro ovicidal and larvicidal activity of extracts of tansy (Tanacetum vulgare L.) growing in Latvia on gastrointestinal nematodes (Trichostrongylidae) in sheep. The leaves and flowers of the tansy were extracted separately in 70%, 50%, and 30% ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A study of the human gut microbiome showed positive effects of condensed tannins [ 66 ]. Ruminants can benefit from tannin intake as it reduces bloating and intestinal parasites [ 64 , 68 ]. Tannin metabolism and its relationship with the gut microbiome is complex due to tannins’ structural diversity and high molecular mass.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the human gut microbiome showed positive effects of condensed tannins [ 66 ]. Ruminants can benefit from tannin intake as it reduces bloating and intestinal parasites [ 64 , 68 ]. Tannin metabolism and its relationship with the gut microbiome is complex due to tannins’ structural diversity and high molecular mass.…”
Section: Discussionmentioning
confidence: 99%
“…Ellio [24]. The in vitro anthelmintic activity of various tansy inflorescence and leaf extracts was estimated on Trichostrongylidae nematodes in sheep [25]. The cultivation of tansy (and other perennial wild plant species) is an important factor for sustainable bioenergy (biogas) production [26].…”
Section: Introductionmentioning
confidence: 99%